The secret garden [videorecording (DVD)] - Thorne, Jack; Egerickx, Dixie, 2005-; Firth, Colin, 1960-; Walters, Julie, 1950-; Hayhurst, Edan; Wilson, Amir, 2004-; Davis, Isis; Dermody, Maeve; Marianelli, Dario; Crawley, Lol, 1974-; Burnett, Frances Hodgson, 1849-1924 (Universal Pictures Home Entertainment, 2020)
Mary Lennox is a prickly and unloved ten-year-old girl, born in India to wealthy British parents. When they suddenly die, she is sent back to England to live with her uncle. There, she begins to uncover many family secrets, particularly after meeting her sickly cousin Colin, who has been shut away in a wing of the house. Together, these two damaged, slightly misfit children heal each other through their discovery of a wondrous secret garden.